Looking at the Beauty of Halal Through The Stimulus-Organism-Response Model and Gender Perspectives: The Case of Indonesian Muslim - Sri Rahayu Hijrah Hati; Rakotoarisoa Maminirina Fenitra; Adlin Masood; Hapsari Setyowardhani; Alina Abdul Rahim; Ujang Sumarwan (Emerald, 2026)
Indexed by WOS/Scopus/ERA